More Giving or More Givers? The Effects of Tax Incentives on Charitable Donations in the UK - Miguel Almunia; Benjamin Lockwood; Kimberley Ann Scharf (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper estimates the tax-price elasticity of giving using UK administrative tax return data, exploiting variation from a large tax reform. We estimate both the intensive and extensive-margin elasticity, using a novel instrumental variables strategy. Then, we derive new conditions to evaluate the welfare consequences of changes in the generosity of the subsidy to donations. We find a small intensive-margin elasticity of -0.2 and a substantial extensive-margin elasticity of -0.8, yielding a total elasticity of about -1. These estimates mask considerable heterogeneity: high-income individuals respond more on the intensive margin, while the extensive-margin response is stronger among low-income taxpayers.
Keywords: H24; H31; D64; 330; tax policy; charitable giving